A first acoustic density estimate for sperm whales in Irish offshore waters - Gordon, Jonathan; Gillespie, Douglas; Leaper, Russell; Lee, Arthur; Porter, Lindsay; O’Brien, Joanne; Meade, Rossa; Ã“ Cadhla, Oliver; Berrow, Simon (J. Cetacean Res. Manage., 2020)
Previous studies off western Ireland have suggested that substantial numbers of, mainly male, sperm whales may be found in these habitats. Whaling vessels operating from shore stations in Ireland in the early 20th century frequently caught sperm whales in oceanic waters. It is likely that this North Atlantic region contains important foraging habitats for this species, and that mature males must also migrate through this area moving between breeding grounds to the south and other feeding areas further north. Increasingly, these offshore waters are being utilised and potentially impacted by human industrial activities. For example, as inshore resources are depleted and technology improves, both the commercial fishing and the oil and gas industry are becoming more active in deeper waters beyond the continental margin. It is important therefore to better understand the biology and ecology of sperm whales in these more remote areas. However, their offshore location and deep diving habits, together with weather constraints in the exposed Atlantic, make research difficult. New sperm whale density estimates are reported using data from six seasonal passive acoustic surveys carried out in two successive years (2015 and 2016). These covered a corridor approximately 110km wide which bounded a major portion of Ireland’s continental shelf break. Towed hydrophone line-transect methodologies were used, which have proven to be highly effective for surveying sperm whales in offshore waters and in poor weather conditions. Target motion analysis was applied to calculate the ranges of vocalising whales from the survey tracklines and the effective strip half-width calculated across all surveys was 7,958m. The study area was surveyed in three blocks and animal densities within these blocks varied between 1 and 4.6 individuals per 1,000km2 (CV 0.34 and 0.21 respectively) with an overall mean density in waters deeper than 300m of 3.2 individuals per 1,000km2 (CV 0.04). These robust density estimates are the first of their kind for Irish waters and are similar to those reported in other Atlantic areas considered significant for this species. These results emphasise the significance of this region as sperm whale habitat. The results of this study should be used to inform the future sustainable development and management of Ireland’s offshore Atlantic.